Sea surface barometry with an O2 differential absorption radar: retrieval algorithm development and simulation - Lin, Bing; Mclinden, Matthew Walker; Cai, Xia; Heymsfield, Gerald M.; Privé, Nikki; Harrah, Steven; Li, Lihua (Frontiers in Remote Sensing, 2024)
Sea surface air pressure observations are a significant gap in current Earth observing systems. This study addresses the retrieval algorithm development and evaluation of potential impacts of instrumental and environmental uncertainties on sea level pressure retrievals for the measurements of O2 differential absorption radar systems operating at three spectrally even spaced close frequency bands (65.5, 67.75 and 70.0 GHz). A simulated northern hemispheric summer case is used to simulate retrieval uncertainties. To avoid high attenuation and low signal-to-noise ratio, radar measurements from weather conditions with rain rate  1 mm/hr are not used in the retrieval. This study finds that the retrieval algorithm combining all three channels, i.e., the 3-channel approach, can effectively mitigate major atmospheric and sea surface influences on sea surface air pressure retrieval.The major uncertainty for sea surface pressure retrieval is caused by the standard deviation in radar power returns. Analysis and simulation demonstrate the potential of global sea surface pressure observations with errors about 1 2 mb, which is urgently needed for improvement of numerical weather prediction models. Future work will emphasize on the instrument development and field experiments. It is anticipated that in few years, an O2 differential absorption radar system will be available for meteorological applications.